Retina nerve fiber layer and choroidal thickness changes in obstructive sleep apnea syndrome. Issue 3 (2nd April 2016) - Ozge, Gokhan; Dogan, Deniz; Koylu, Mehmet Talay; Ayyildiz, Onder; Akincioglu, Dorukcan; Mumcuoglu, Tarkan; Mutlu, Fatih Mehmet
ABSTRACT: Objectives : The purpose of this study was to determine the effects of obstructive sleep apnea syndrome (OSAS) on the submacular and peripapillary retinal nerve fiber layer (RNFL) and choroidal thickness (ChT). Methods : Eighty-four eyes of 42 male patients with OSAS and 112 eyes of 56 aged-matched and body mass index-matched healthy male subjects were enrolled in this case-control study. The ChT and peripapillary RNFL thickness was measured using enhanced depth imaging optical coherence tomography. The ChT and RNFL thickness measurements of the groups were compared, and correlations among the Apnea Hypopnea Index (AHI) values and these measurements were calculated. Right and left eyes were separately evaluated. Results : There were no significant differences in the subfoveal and temporal ChT between the groups (p > 0.05). The OSAS group had significantly thicker ChT at 0.5 and 1.5 mm nasal to the fovea in both eyes than the control group (p < 0.05). The peripapillary ChT were significantly thicker in the OSAS group at all segments except for the temporal and superotemporal segments when compared with the control group (p < 0.05 for all quadrants except temporal and superotemporal). When compared with controls, the OSAS group had significantly thinner nasal RNFL thickness in the right eye (p = 0.01) and thinner mean RNFL thickness in both eyes (p < 0.001). Other RNFL thickness measurements were similar between groups (p > 0.05). Between AHI and mean RNFL thickness showed a median negative correlation (r = − 0.411, p = 0.001). Conclusion : The choroidal thickening in patients with OSAS may be associated with the pathophysiology of the neurodegeneration process of the disease.